Influence of repeated plaque visualization on cardiovascular risk reduction after 3 years : a randomized controlled trial - Whitmore, Kristyn; Zhou, Zhen; Ryan, Jacqueline D. M.; Magnussen, Costan G.; Carrington, Melinda J.; Marwick, Thomas H.; CAUGHT CAD investigators (OXFORD UNIV PRESS, 2025)
Aims
Helping people to understand their cardiovascular (CV) risk can influence the choices they make for risk reduction, including medication adherence and lifestyle modification. This study sought whether repeated visualization of coronary artery calcium (CAC) images was effective in sustaining long-term risk control in primary prevention, independent of a risk reduction programme.
Methods and results
Asymptomatic, statin-na & iuml;ve participants, 40-70 years, with a family history of premature coronary artery disease and a CAC score from 1-400 were randomized to a nurse-led CV risk reduction programme or standard care with bi-annual reviews. Only the intervention group (220 of 449 participants) visualized their CAC image (with repeat exposure in the first 3 months) and were initiated on statin therapy. The primary outcome was change in Framingham Risk Score (FRS) at 36 months, and the impact of CAC image recall on CV risk was assessed. The reduction in FRS (difference in differences (DID) -3.4% [95% CI: -4.4% to -2.4%], P <= 0.001 and low density lipoprotein cholesterol -1.2 mmol/L [95% CI: -1.4 to -1.0], P <= 0.001) over 36 months was greater in the intervention than the control group. Within the intervention group, sustained recall of CAC images at 24 months was associated with lower systolic blood pressure (DID -4.3 mmHg [95% CI: -7.7 to -0.9], P = 0.01) and waist circumference (DID -2.0 cm [95% CI: -3.9 to -0.1], P = 0.03) at 36 months compared to unsustained recall.
Conclusion
A nurse-led programme, combining personalized patient visualization of CAC imaging with statin therapy, is beneficial for improving CV risk. Recalling the presentation of CAC images through repeated visual exposure may influence risk reduction.
Registration
Australia New Zealand Clinical Trials Registry: ACTRN12614001294640
Lay summary
​​​​​​​This trial sought to determine whether visualization of coronary artery calcium (CAC) images influences behaviour change and cardiovascular risk reduction within a structured nurse-led programme vs. standard care.
Intervention participants visualized their personalized CAC images within the first three months and commenced statin therapy. Control participants were blinded to their CAC images and were not provided statin therapy. Intervention participants had a greater absolute reduction in the Framingham Risk Score (difference in differences -3.4% [95% CI: -4.4% to -2.4%], P <= 0.001) compared to controls.
Those with sustained recollection of their CAC images within the intervention group also had greater reductions in systolic blood pressure and waist circumference.